In/sicurezza fra i banchi Bullismo, omofobia e discriminazioni a scuola: dati, riflessioni, percorsi a partire da una ricerca nelle scuole secondarie umbre - Batini, Federico; Scierri, Irene Dora Maria (Il mestiere della pedagogia, 2021)
School is where children and youth spend most of their time, where they learn, socialise and grow. However, multiple pieces of evidences tell us that school is not always a safe 'place' for everyone. This book explores the phenomenon of school bullying, focusing in particular on homophobic bullying, and has been developed from the results of regional research conducted in secondary schools in the Region of Umbria and extends to the national and international background, with a reflexive-interpretative approach to the data on the occurrence of the phenomenon, best practices and guidelines. Bullying is an educational problem − of inclusion, equity and safety − that is relevant for every parent, teacher, headmaster and political executive at the systemic level. From this perspective, the book combines empirical research, theoretical reflection and didactic contextualisation, drawing attention to the need for appropriate gender and civil rights education as a prerequisite for preventing and combating bullying and every form of discrimination.